Stress Analysis of Pelton Turbine Distributor Using UG-NX Software - Lal Pal, Chaman; T.S. Desmukh, Dr.; V.K.Gahlot, Dr. (International Journal of Engineering and Technology, 2018)
The main objective of this paper is analysis of stress in the distributor to find out optimum thickness for safe and satisfactory working at different load condition. To describe how different plate segments required fabricating wyes branches to ensure greater reliability. The distributor of Pelton turbine consists of pipe segments and wyes branches which are then connected to nozzle. A wyes branch, where the distributor bifurcates has a very complex shape and is very difficult to design. A practical case of distributor of 6 jets vertical Pelton turbine of 43 MW power has been carried but using UG-NX software.Â